Prevalence, Risk Factors, and Treatment Strategies of Polycystic Ovary Syndrome at Various Hospitals, Palakkad: A Prospective Study - C. I. Sajeeth, Renatt .C. Francis,; N.M., Mini (International Journal of Innovative Research in Medical Science, 2017)
Aim and Objectives: To monitor and assess the prevalence, risk factors, and treatment strategies of polycystic ovary syndrome. Materials and Methods: A prospective study was conducted in various hospitals of Palakkad from November 2016- April 2017. A total of 207 cases were collected. Patients of age between 15-50years with polycystic ovary syndrome were included in the study. Results and Discussion: The maximum number of patients belongs to 21-25 years. Risk factors of study population include hypothyroidism (69%), followed by cardiovascular disease, obesity, migraine etc. Medroxy progesterone (30%), Clomiphene citrate (23%), Ethinyl estradiol (16%), Metformin (15%) etc are given as treatment for PCOS. Conclusion: From the study it shows that the prevalent age group is 21-25 years. Hypothyroidism is the major risk factor for PCOS. Current treatment strategies include medroxy progesterone, clomiphene citrate, followed by ethinyl estradiol and metformin.